2022
DOI: 10.1097/pr9.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of pain and function after knee replacement: a systematic review and meta-synthesis of qualitative studies

Abstract: Supplemental Digital Content is Available in the Text.Patient perspectives highlight the need for presurgical information about expected recovery trajectories after total knee replacement and enhanced postsurgical follow-up with practical support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
(514 reference statements)
0
9
0
Order By: Relevance
“…Survey-based research has shown postoperative pain (and mobility) to be of the most prominent concerns 32 33. A systematic review and meta-synthesis of 28 qualitative studies demonstrated patients did not understand what the normal resolution of pain should be postoperatively 34. Clinicians should be aware of this, in ensuring effective pain management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survey-based research has shown postoperative pain (and mobility) to be of the most prominent concerns 32 33. A systematic review and meta-synthesis of 28 qualitative studies demonstrated patients did not understand what the normal resolution of pain should be postoperatively 34. Clinicians should be aware of this, in ensuring effective pain management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinicians should take care to explain and give reasonable expectations for pain and function, in particular mobility. Meta-synthesis of qualitative research has demonstrated that this information is not always conveyed 34. Better communication and individual assessment of needs has been suggested to improve care 11 57.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Motivating patients in rehabilitation after TKA can be challenging because progress is gradual, variable, and often painful. [6][7][8] Positive reinforcement via the tool may increase patient motivation to participate in rehabilitation and support patients to meet their personal goals after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] Most reviews assess only postoperative outcomes, which may be affected by surgery quality, postoperative complications, pain, mismatch of expectations, and motivation to return to rehabilitation. 31 Prehabilitation varies substantially in content and is currently predominantly home-based. No previous reviews have examined the effects of home-based exercise programmes but include studies with heterogeneous interventions.…”
Section: Table I Continuedmentioning
confidence: 99%